Colorectal cancer-related resource utilization and healthcare costs in Saudi Arabia - Bander Balkhi; Ahmed Alghamdi; Saeed Alqahtani; Marwan Al Najjar; Abdullah Al Harbi; Thamer Bin Traiki (Saudi Pharmaceutical Journal)
Background: Recently, there has been an increase in the incidence of colorectal cancer in Saudi Arabia. Although numerous studies worldwide have investigated the economic burden of colorectal cancer the information specific to Saudi Arabia remains limited. While advanced cancer treatments offer substantial benefits, they they also come with substantial financial challenges. Objective: This study aimed to estimate the economic burden of colorectal cancer and identify the primary cost drivers. Method: This retrospective, single-center cost of illness study examined all patients with colorectal cancer from January 2017 to December 2020. This study used a micro-costing, bottom-up approach to estimate healthcare resource utilization and direct medical costs associated with colorectal cancer. Result: The study included 326 patients with colorectal cancer. The total direct medical cost for all patients were $19 million, with an annual cost per patient of $58,384. Medication costs were the primary driver of healthcare spending (45%) of the total cost, followed by surgical costs (27%). This study explained cost associated with colorectal cancer, which represents a significant cost to the Saudi healthcare budget. The expected growth and aging of the population and availability of costly treatments may lead to an increase in costs. These findings are valuable for healthcare policymakers seeking to comprehend the economic challenges posed by colorectal cancer.